Upaya Meningkatkan Prestasi Belajar Peserta Didik Pada Mata Pelajaran PAI Dengan Menggunakan Metode Pembelajaran Make a Match di Kelas IV SD Negeri 18 Pasar Cubadak - Helyatina, Helyatina (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to determine the effect of the Make a Match method on improving the learning achievement of Islamic Religious Education (PAI) in class IV of SDN 18 Pasar Cubadak. The research uses a descriptive qualitative approach with data collection techniques through observation, interviews, documentation, and tests. Based on the observations in Cycle I and Cycle II, it was found that the application of the Make a Match method can improve students' activity and learning outcomes. In Cycle I, although there was an improvement, the results were not optimal, whereas in Cycle II, a significant increase occurred, with 100% of students achieving learning completeness. This study concludes that the Make a Match method is effective in improving students' learning achievement in PAI lessons